Abundances of small microplastics (S-MP, 11-500 μm) in surface waters of the Weser estuary and the German North Sea (April 2018) - Lisa Roscher; Annika Fehres; Lorenz Reisel; Maurits Halbach; Barbara Scholz-Böttcher; Michaela Gerriets; Thomas Henry Badewien; Gholamreza Shiravani; Andreas Wurpts; Sebastian Primpke; Gunnar Gerdts (PANGAEA, 2021)
In order to assess pollution with small microplastics (S-MP, 11-500 μm) in the Lower Weser and transition to the German North Sea, surface water samples were collected with the RV Otzum (ICBM, Institute for Chemistry and Biology of the Marine Environment), as well as with the RV Uthörn (AWI, Alfred-Wegener-Institute) in April 2018. Sampling was performed using a pumping system containing of a floating suction basket (mesh size: 500 μm) for pre-filtration, followed by the concentration onto a 15 μm stainless steel screen. Samples were isolated from the filter screens in the laboratory, thoroughly processed and measured via μFTIR imaging. Dominant polymer type in the S-MP sample fraction was acrylates/polyurethanes/varnish, and concentrations ranged between 2.3 exttimes 10^1 and 9.7 exttimes 10^3 m?^3, with maximum values in the area of the turbidity Maximum Zone of the River Weser.